Hubungan Sindrom Metabolik Dengan Preeklampsia di Puskesmas Majasem - Husnaa, Farah Syaufika; Suroso, Triono Adi; Ahmad, Zulkifli (Syntax Corporation, 2024)
Preeclampsia is a pregnancy-induced hypertension accompanied by proteinuria or other organ system disturbances. The incidence of preeclampsia in Indonesia is 128,273 per year or around 5.3%, with no apparent decrease in cases over the last two decades. Several risk factors can contribute to the development of preeclampsia, one of which is obesity, a metabolic disorder in the body and a clinical manifestation of metabolic syndrome. This study aims to determine the incidence of metabolic syndrome in postpartum mothers with a history of preeclampsia, understand the incidence of preeclampsia, and analyze the relationship between metabolic syndrome and preeclampsia at Majasem Community Health Center in 2022. The study utilizes an analytical observational method with a cross-sectional approach. Data used are medical records of postpartum mothers in 2022 at Majasem Community Health Center. The total sampling method was employed, resulting in 40 research samples. Bivariate analysis using Spearman's correlation test indicates that the number of postpartum mothers experiencing metabolic syndrome is 16. The total number of preeclampsia cases at Majasem Community Health Center is 40. The Spearman test results show a significant relationship between metabolic syndrome and preeclampsia, with a p-value of 0.018 < 0.05.